The Influence of the Supervision of the Head on the Performance of Nurses in the Medan Hajj General Hospital - Ibnu Fuqon; Asriwati Amirah; Jamaluddin Jamaluddin; Lucia Lastiur (Newinera Publisher, 2021)
A study conducted by the Directorate of Nursing Services, Ministry of Health of the Republic of Indonesia (2011) found that the nursing services provided by nurses to patients had not reached the set target, namely a minimum figure of 75% of the nurse's performance was said to be good.This type of research is quantitative, with adesign cross-sectional which aims to see the effect of headroom supervision on the performance of nurses in the inpatient room of the General Hospital Hajj Medan in 2020. The sampling technique used is proportioanl stratified random. sampling. Data collection using primary data by distributing questionnaires to the nurse administrators and secondary data obtained from the hospital, namely the hospital profile. Data analysis used Chi square test (α = 0.05) and multiple linear regression.The results showed that the variables that influence the performance of nurses are planning (p = 0.000), guiding (p = 0.045), monitoring (p = 0.000), evaluation (p = 0.002), recording and reporting (p = 0.000). The variables that did not affect the nurse's performance were organizing (p = 0.382) and directing (p = 0.065). In conclusion, the most influential variable is recording and reporting with the highest coefficient value, amounting to 1.674 with a positive value. It is recommended that the head of the room carry out supervision in a programmed, scheduled manner, in accordance with the standards and principles of its implementation and optimize recording and reporting in supervision activities.